PENGELOLAAN PONDOK PESANTREN BERBASIS KEMANDIRIAN KURIKULUM DI PONDOK PESANTREN AN NAHL KUBANG TUNGKEK - Anton; Marjoni Imamora; Sirajul Munir; Ridwal Trisoni; Demina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This thesis research aims to provide a descriptive overview and analysis of the planning and management, implementation and evaluation of the implementation of the Independence Curriculum at the An-Nahl Kubang Tungkek Islamic Boarding School. Type of field research (field research) qualitative research with a descriptive approach to maintaining curriculum independence at the An-Nahl Kubang Tungkek Islamic Boarding School. The data sources in this research are primary data and secondary data which discuss the management of curriculum independence at the An-Nahl Kubang Tungkek Islamic Boarding School. The results of this study indicate that: First, curriculum planning at An-Nahl Islamic Boarding School begins with the identification of educational needs according to the vision and mission of the institution. The planning team, consisting of foundation administrators, principals, and teachers, formulates curriculum objectives to form santri who are knowledgeable, noble, and have strong faith. Second, curriculum organization involves the formation of a curriculum team consisting of the principal, vice principal for curriculum, teaching staff, and administrative staff, as well as the establishment of a curriculum structure that includes subjects, materials, schedules, and teaching methods according to the needs and potential of the students. Third, the implementation of an independent curriculum shows its distinctiveness by combining two curricula and active extracurricular activities, as well as funding support to support santri achievement, then the independent curriculum is divided into three groups: Group A (general subjects such as Religious Education, Mathematics, and English), Group B (Physical Education, Workshops, and Cultural Arts), and Group C (character development and practical skills). Fourth, the implementation of curriculum evaluation at An-Nahl Islamic Boarding School involves weekly, monthly, and end-of-semester meetings with the participation of all educational elements, especially teachers, with direct observation methods, assessment of santri learning outcomes, and feedback from teachers and santri. Keywort : Islamic Boarding School Based On Curriculum Independence